Implementation of Cultural School at SMAN 1 Parakan - Aisjah (International Journal of Post Axial: Futuristic Teaching and Learning, 2023)
The purpose of this research is to describe the implementation of a cultural school at SMAN 1 Parakan. This study is a qualitative case study conducted at SMAN 1 Parakan in Temanggung Regency. Data collection methods used in this research include documentation, observation, and interviews. The focus of this research is on character strengthening by emphasizing cultural values and local wisdom. The results of this research reveal that the cultural school implemented at SMAN 1 Parakan utilizes the following strategies: policy, integration of intra, co-, and extracurricular activities, habituation, artifact of learning, involvement of parents and the community, and publication.